Symmetry and Asymmetry in the Structure of Temporal Opposition “Past / Future” (based on Media Texts) - I. N. Ponomarenko; N. A. Segal; Y. N. Bychina; S. A. Mospan (Научный диалог)
The article is devoted to the identification of the asymmetric basis of explication of temporal oppositions in the Russian-language media discourse. The semantic-pragmatic potential of linguistic units representing the antithesis of “past / future” and its textual explicators is established and analyzed. Given the specifics of linguistic and extralinguistic factors, the features of modeling the current political picture of the world are revealed. It is emphasized that the asymmetry of the media discourse, which has become the subject of scientific research only in the last decade, is dictated by the manipulative orientation of media texts. An analysis of practical material allows us to conclude that the media texts of the beginning of the XXI century are a priori asymmetric and are built on both communicative and linguistic asymmetries, which consist primarily in the contraposition of linguistic and contextual antonyms that reflect polar political views and aspirations. The asymmetry of images of the past and future and the ambiguity of connotations inherent in the linguistic representatives of these images allow us to talk about the variability of the value component of the key categories of the political picture of the world and prove its dynamic nature.